Bandwidth Enhancement of an Array Antenna using Slotted Artificial Magnetic Conductors - H., Lago; Mohd Faizal, Jamlos; Ping, Jack Soh; M. H., Muslim; Vandenbosch, Guy A. E.; Narbudowicz, Adam (Springer Berlin Heidelberg, 2017)
An artificial magnetic conductor (AMC)-integrated array antenna operating at 9.41 GHz is proposed in this work. The AMC plane consists of an array of 9 × 12 rectangular elements slotted using four circular slots. The rectangular circular-slotted AMC unit cell acts as a metamaterial with high permeability of 10.05 and non-unity permittivity of 1.52, respectively. The integration of the AMC plane into a reference array antenna operating at 9.41 GHz increases the impedance bandwidth by 76%, from 1.12 to 1.98 GHz. Besides that, the efficiency is also enhanced from 95.91 to 96.31%. Both reference and proposed antenna show a satisfactory agreement in terms of simulated and measured reflection coefficients and radiation patterns.